2018
DOI: 10.1037/neu0000400
|View full text |Cite
|
Sign up to set email alerts
|

Emotion recognition in Parkinson’s disease: Static and dynamic factors.

Abstract: PD participants may have subtle emotion recognition deficits that are not ameliorated by the addition of contextual cues, similar to those found in everyday scenarios. Consistent with previous literature, the results suggest that PD participants may have underlying emotion recognition deficits, which may impact their social functioning. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
7
1
Order By: Relevance
“…We find a worse EFE recognition ability in the PD_CogDec group compared to HC both for static and dynamic EFE tasks, while the PD_CogInt group's performance was only worse than that of HC in the static task. This last result contradicts the findings of Wasser et al (2018), who did not find differences between PD and HC, either for static or dynamic tasks. However, they did observe a trend towards a worse performance in PD than in the HC group in both tasks, and the difference with our results could arise from the fact that these authors did not differentiate patients based on their cognitive status.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…We find a worse EFE recognition ability in the PD_CogDec group compared to HC both for static and dynamic EFE tasks, while the PD_CogInt group's performance was only worse than that of HC in the static task. This last result contradicts the findings of Wasser et al (2018), who did not find differences between PD and HC, either for static or dynamic tasks. However, they did observe a trend towards a worse performance in PD than in the HC group in both tasks, and the difference with our results could arise from the fact that these authors did not differentiate patients based on their cognitive status.…”
Section: Discussioncontrasting
confidence: 94%
“…Although in PD patients difficulties to recognize EFEs have been observed with both static and dynamic stimuli (Argaud et al, 2016;Kan, Kawamura, Hasegawa, Mochizuki, & Nakamura, 2002;McIntosh et al, 2015), only two studies have compared the patients' performance with both types of stimuli, with contradictory results. Whereas Wasser et al (2018) did not observe any differences between patients and controls for either static or dynamic stimuli, Kan et al (2002) reported that their patients' recognition of static stimuli was less accurate than their recognition of dynamic stimuli.…”
Section: Introductionmentioning
confidence: 77%
“…Although more and more researchers pay attention to multimodal emotion recognition technology, the overall emotion recognition rate is relatively low, which is not enough to be applied in real life. Therefore, multimodal emotion recognition will be the key research part in emotion computing [ 23 , 24 ].…”
Section: Related Workmentioning
confidence: 99%
“…There is substantial evidence that incorrect recognition and misinterpretations of emotional facial expressions is associated with impairments in social functioning, such as diminished social competence, poor social communication and inappropriate interpersonal behavior [3,4]. Impaired recognition of emotional facial expressions has been documented in various neurological patient groups, including traumatic brain injury (TBI, [5][6][7]), stroke [8][9][10], and various neurodegenerative disorders, such as Alzheimer's disease (AD, [11,12]), frontotemporal dementia (FTD, [13,14]), and Parkinson's disease (PD, [15,16]). At present, measurements of social cognition (i.e.…”
Section: Introductionmentioning
confidence: 99%